Decoding the Mechanism of Huanglian Jiedu Decoction in Treating Pneumonia Based on Network Pharmacology and Molecular Docking - Li, Xianhai; Tang, Hua; Tang, Qiang; Chen, Wei (Frontiers in Cell and Developmental Biology, 2021)
Huang-Lian-Jie-Du Decoction(HLJDD) has been used to treat pneumonia for thousands of years in China. However, our understanding of its mechanisms on treating pneumonia is still in unclear. In the present work, the network pharmacology was used to analyze the potential active ingredients and molecular mechanisms of HLJDD on treating pneumonia. A total of 102 active ingredients were identified from HLJDD, among which 54 were hit by the 69 targets associated with pneumonia. By performing GO and KEGG enrichment analysis, we obtained the main pathways associated with pneumonia and that associated with the mechanism of HLJDD in the treatment of pneumonia. By constructing the protein-protein interaction network of common targets, 10 hub genes were identified, which were mainly involved in TNF signaling pathway, IL17 signaling pathway, and NOD like receptor signaling pathway. Moreover, results of molecular docking showed that the active ingredients of HLJDD had a good affinity with the hub genes. The final results indicate that HLJDD have a greater effect on bacterial pneumonia than viral pneumonia. The therapeutic effect is mainly achieved by regulating the host immune inflammatory response and oxidative stress reaction, anti-bacterial microorganisms, alleviating the clinical symptoms of pneumonia, repairing damaged cells and inhibiting cell migration.